2004
DOI: 10.1111/j.1551-2916.2004.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor Behavior of the 0.9BaTiO3–0.1La(Mg1/2Ti1/2)O3 Solid Solution

Abstract: Low‐frequency dielectric response of air‐ and oxygen‐sintered ceramics with the composition 0.9BaTiO3–0.1La(Mg1/2Ti1/2) O3 (0.9BT–0.1LMT) has been studied in the temperature range of 12–550 K. In comparison with pure BT, in 0.9BT–0.1LMT the dielectric permittivity maximum is shifted by almost 300 K toward lower temperatures. Both real and imaginary parts of dielectric permittivity of the solid solution, in the range 12–150 K, show a strong frequency‐dependent behavior, which is typical of relaxors. On the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For heterovalent substitution on the A-site relaxor behavior is induced at moderate doping levels (e.g., x = 0.10 for Ba 1Àx Bi 2x/3  x/3 TiO 3 70 The latter systems are of particular interest. 62,63]. Second, appearance of the relaxor behavior in systems without nominal charge disorder is unique and has not been well understood so far.…”
Section: Lead-free Relaxor Systemsmentioning
confidence: 99%
“…For heterovalent substitution on the A-site relaxor behavior is induced at moderate doping levels (e.g., x = 0.10 for Ba 1Àx Bi 2x/3  x/3 TiO 3 70 The latter systems are of particular interest. 62,63]. Second, appearance of the relaxor behavior in systems without nominal charge disorder is unique and has not been well understood so far.…”
Section: Lead-free Relaxor Systemsmentioning
confidence: 99%
“…It is characterized by a monoclinic perovskite structure (Z = 4, space group P2 1 /n) due to oxygen octahedra tilting and B-site cation (Mg/Ti) ordering [8]. It has been shown that small additions of LMT modify strongly the dielectric response of BT, decreasing the transition temperature to a paraelectric phase about 30 K/1 mol% of LMT [11]. Ceramics of the BT-LMT system were found to exhibit mainly relaxor features at doping levels as low as 5 mol% of LMT.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that BT ceramics doped with 2.5 mol.% of LMT exhibit the typical features of both the ferroelectric and the relaxor, 3 while BT-10% LMT demonstrates solely the relaxor properties. 4 Dielectric investigations of BT-LMT performed by the macroscopic methods (averaging over many grains) and on the nanoscale level (in a single grain) have proved the presence of polar nanoregions in the ceramics at temperatures above the dielectric permittivity peak. 4,5 Recently, homogeneous ceramics (1 − x)BaTiO 3 -xLa(Mg 1/2 Ti 1/1 )O 3 ((1 − x)BT-xLMT) with the compositions x = 0.025, 0.05, 0.075 and 0.1 were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…4 Dielectric investigations of BT-LMT performed by the macroscopic methods (averaging over many grains) and on the nanoscale level (in a single grain) have proved the presence of polar nanoregions in the ceramics at temperatures above the dielectric permittivity peak. 4,5 Recently, homogeneous ceramics (1 − x)BaTiO 3 -xLa(Mg 1/2 Ti 1/1 )O 3 ((1 − x)BT-xLMT) with the compositions x = 0.025, 0.05, 0.075 and 0.1 were obtained. The X-ray diffraction studies 6 have revealed the tetragonal (P4mm) perovskite structure for the compositions with x < 0.025 and the cubic (Pm3m) for x > 0.05 at the room temperature.…”
Section: Introductionmentioning
confidence: 99%